FUNGSI TARI KELIK LANG DALAM UPACARA ADAT PERKAWINAN DI KELURAHAN PULAU TEMIANG KABUPATEN TEBO - Ari Fatmawati; desfiarni desfiarni; Afifah Asriati (FBS Universitas Negeri Padang, 2013)
Abstract This article aims to reveal and explain the function of Kelik Lang dance in a traditional wedding ceremony in Pulau Temiang village especially in Tebo Ulu regency. The types of this research are qualitative and descriptive method. The data collected by a literature study, observation, interviews, photo shoot and documentation. The analysis of the data based on the conceptual framework. The result of the research showed that Kelik Lang dance always use in traditional wedding ceremony especially in “Belarak” event before the bride and groom enter the bridge house. The function of Kelik Lang dance are (1) as a media of marriage ceremony (2) as an entertainment and recreational for citizen (3) as an idea or ritual in marriage process (4) as a media to express feeling of soul. Kata kunci: Fungsi, Tari, Kelik, Lang